Hubungan Preeklamsia Dengan Kejadian Asfiksia Neonatorum Di Rumah Sakit Ibu Dan Anak Cinta Kasih - Sinabutar, Nerli Adria; Kartikasari, Rizky Fitria; Maryati, Maryati (Jurnal Kesehatan STIKes IMC Bintaro, 2023)
ABSTRACT Introduction: Preeclampsia is hypertension that occurred after 20 weeks of gestational age and accompanied with proteinuria. Preeclampsia runs into vasoconstriction in blood vessels thus affecting the decreasing of blood flow in the uterus which causes the decreasing of oxygen flow to the placenta and fetus, therefore, hypoxia happened in the fetus that effects asphyxia neonatorum. The purpose of research: Knowing correlation of preeclampsia with asphyxia neonatorum case at cinta kasih mother and child hospital ciputat in 2020. Research method: using Cross Sectional approach method. The population i.e. all mothers who gave birth in cinta kasih mother and child hospital ciputat in 2020. The sample of this research as many as 82 respondents that determined with systematic random sampling technique. The research of instrument in the form of observation sheet. Analysis data of research using Chi Square test. Result of research: showing that from 82 respondents, 65 people (79,3%) don’t get preeclampsia, and 17 people (20,7%) get preeclampsia. From 17 preeclampsia respondents, 7 people (41,2%) don’t give birth to preeclampsia babies, and 10 people (58,8%) gave birth to preeclampsia babies. Conclusion: There’s a correlation between preeclampsia with asphyxia neonatorum case (P Value = 0,003). Suggestion: hoping the nurses be able to do promotive and preventive efforts to decrease the number of death as a result of asphyxia neonatorum also increasing high quality in nursing care.